Ação antiofídica da creolina® frente a peçonha de bothrops jararaca em ratos: aspectos clínicos, hematológicos e histopatológicos - Carvalho, Lucas Rannier Ribeiro Antonio (2019)
Snakebites represent a serious one health problem in the world, as well as economic losses in animal production systems. In Brazil, snakes of the genus Bothrops are responsible for most accidents. The specific treatment recommended in Brazil is the use of pentavalent antibotropic serum associated to the symptomatic auxiliary treatment, according to the severity of the accident. However this therapeutic treatment presents difficulties in obtaining and distribution, high cost, considerable immunological reactions and is not effective against to local tissue damage caused by venom. Therefore, new therapies that treat the effects of venom and/or complement the serum therapy are necessary. This study aims to evaluate the possible antiofidic activity of Creolin® against Bothrops jararaca venom. In adult Wistar rats, the bothropic venom was inoculated intramuscularly and immediately after administration of Creolin® orally, topically, intramuscularly, and the mixture: (Venom + Creolin®), intramuscularly. The animals were clinically evaluated for eight hours, then euthanized for collection of blood and tissue samples. Groups that had oral, topical, and muscle contact with Creolin® separately developed local symptomatology and laboratory findings similar to those receiving only the venom. However, the animals inoculated with the venom with Creolin® in a mixture did not show signs of local venom action (necrosis, hemorrhage) and presented hematological parameters within the normal range. These results suggest that Creolin® alone does not present antiofidic action, but when mixed the bothropic venom can partially inactivate its bioactive components. Therefore, more studies are needed to evaluate this alternative therapy used empirically.